Peripheral Arteriovenous Malformation Embolization Using Squid - Saima Ahmad; Moeez Uddin (Case Reports in Vascular Medicine)
Background and Objectives. Head and neck arteriovenous malformations and fistulae treatment without reflux and with nidal penetration can pose a particular challenge to the interventional radiologist. Squid, an ethylene-vinyl alcohol copolymer-based liquid embolic agent, was developed primarily for neuroradiologic interventions with limited applicability being described in the management of peripheral arteriovenous malformations. We present a study evaluating the safety and efficacy of using squid (18 and 12) alone and in combination with other embolic agents for peripheral arteriovenous malformation embolization in a cohort of adult and paediatric patients. Materials and Methods. Between January 2018 and December 2020, twenty patients (7 men and 13 women) with peripheral high-flow arteriovenous malformations who were treated primarily with arterial embolization using squid were retrospectively included. Anatomical sites being treated included the head and neck (16), extremities (2), uterus (1), and pelvis (1). Squid was used as the sole embolic agent in 15 patients, and transarterial embolization was employed in all cases except one where direct puncture embolization was used. Treatments were delivered over one or two sessions, with or without surgery. A total of 27 sessions were carried out with an interval time ranging from 6 to 36 months between sessions. Results. Technical success was achieved in all cases. In those patients treated with squid alone, 13 exhibited total devascularization following embolization, and a further 4 required surgical excision to achieve complete obliteration of the arteriovenous malformation. There were no major complications, cases of microcatheter entrapment, or dimethyl sulfoxide-related pain recorded. On follow-up, one patient reported persistent pain, and another patient developed a garlicky taste. All other patients reported complete resolution of symptoms following treatment. Conclusion. This study demonstrates the successful use of squid in managing peripheral arteriovenous malformations with low complication rates and long-term stable results, therefore validating its efficacy when used alone or in combination with other embolic agents. Squid may be the preferred embolic agent in any interventional radiologist’s armamentarium as it offers formulations with varying viscosities (squid-18 and squid-12). We conclude that squid should be considered as a first-line embolic agent in the management of peripheral arteriovenous malformations.